Belle Prater's boy - White, Ruth, 1942- (New York : Farrar Straus Giroux, 1996)
When Woodrow's mother suddenly disappears, he moves to his grandparents' home in a small Virginia town where he befriends his cousin and together they find the strength to face the terrible losses and fears in their lives.
Keywords: Cousins -- Fiction; Mother and child -- Fiction; Loss (Psychology) -- Fiction; Identity -- Fiction